Qada Zakat: Suatu Perbincangan Menurut Hukum Syarak: Qada’ Zakah: A Discussion According to Islamic Law - Syed Fadil, Syed Muhammad; Daud, Mohd Zaidi; Jamaludin, Mohd Hafiz (Jurnal Fiqh, 2022)
According to Islamic law, Muslims who have complete the full period of an Islamic year (hawl) must pay zakah. It can, however, be found among Muslims who negligently fail to pay zakah within the stipulated period. Every obligatory practise must be performed within the time determined by Allah SWT in the discourse of fiqh. Hence, this article will look at the aspect of qada’ zakah in view of the shara‘ discussion. Thematic content analysis of themes based on the schools of thought will be used to thoroughly discuss this topic. In conclusion, Shariah allows and provides exemption to zakah payers in unavoidable situations. As a result, zakah should be paid even if it is not within the timescale provided if there is justification allowed by shara‘.